Potensi Hasil Hutan Suku Wemale Nuduasiwa Patai Kabupaten Seram Bagian Barat - Johan M Matinahoru (Fakultas Pertanian, Universitas Pattimura, 2020)
The tribe of Wemale Nuduasiwa Patai (WNP) is located in the two administrative areas, namely:Inamosol and Kairatu districts, West Seram District. Furthermore, in the Inamosol district, thereare five villages of the WNP tribe, namely: the villages of Ursana, Sokowati, Honitetu, Imabatai,and Rumahtita. Whereas in the Kairatu district there is only one village of the WNB tribe, namely:Uraur village. The size of this tribal area is about 300,000 hectares with hilly to mountainoustopography at an altitude of 5 - 1000 m above sea level. The main forest products are the carpentrywood species, such as Shorea sp, Pterocarpus indicus, Vitex gofasus, Litsea angulata,Anthocephallus macrophylla, Magnolia sp, Palaqium spp, Octomelas sumatrana, Duabanga sp,and Eugenia sp with an average production of 196 m3 per year. While the average production ofnon-timber forest products are for agathis resin 2.2 tons, sago flour 3.3 tons and some fruits suchas durian fruits 13.966, 253 sacks of langsat fruits, and 1.477 forest jack fruits in every year.